Pengaruh Store Atmosphere dan Product Quality terhadap Kepuasan Pelanggan Kopi Sulfan Jakarta Pusat - Reska Neta Febriyana; Fazhar Sumantri; Theysa Sahlani Pratiwi (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze the influence of store atmosphere and product quality on customer satisfaction at Kopi Sulfan Central Jakarta. The research method used a quantitative approach with non-probability sampling technique through accidental sampling of 100 respondents. Data was collected using a questionnaire with a 5-point Likert scale and analyzed using multiple linear regression with SPSS version 27. The results showed that store atmosphere has a positive and significant effect on customer satisfaction (t count 4.408 > t table 1.984; sig. <0.001). Product quality also has a positive and significant effect on customer satisfaction (t count 7.108 > t table 1.984; sig. <0.001). Simultaneously, both variables have a significant effect on customer satisfaction (F count 203.200 > F table 3.090; sig. <0.01). The coefficient of determination shows that store atmosphere and product quality can explain 80.7% of the variation in customer satisfaction. This study concludes that coffeeshop management needs to pay attention to both aspects simultaneously to create optimal customer satisfaction.